An international systematic review of the ICF in education: cross-language comparisons from Chinese, German, Italian, and Portuguese publications - Kang, Lin-Ju; Naude, Alida; Rocha, Andre; Bornman, Juan; Alves, Ines; Maxwell, Gregor Ross; Moretti, Marta; Proyer, Michelle; Shi, Linjun; Zahnd, Raphael (Frontiers in Education, 2025)
The International Classification of Functioning, Disability, and Health (ICF), established by the World Health Organization (WHO), provides a biopsychosocial framework for understanding and addressing human functioning and disability. This systematic review examines the application of the ICF in educational contexts across four non-English languages: Chinese, German, Italian, and Portuguese. The findings reveal significant cross-cultural and linguistic variations in interpretation and implementation, shaped by each country’s socio-political, historical, and educational landscape. By analyzing 54 peer-reviewed publications, this review identifies key practical applications of the ICF in fostering inclusive educational practices. The study highlights how the ICF has influenced a shift from medicalized models of disability toward holistic, participation-centered approaches. Specifically, the ICF is used in Chinese literature to guide activity-based assessments in special education, in German studies as a broad theoretical framework, and in Italian and Portuguese research as a practical tool for inclusive education in mainstream settings. Despite its potential, challenges remain in cross-cultural integration, including inconsistencies in adoption and the need for deeper application beyond theoretical references. To enhance the ICF’s impact in education, this review underscores the necessity for training, cross-cultural collaboration, and policy refinement. Strengthening educators’ and policymakers’ understanding of ICF principles can facilitate its integration into mainstream education, ensuring a more inclusive and supportive learning environment for students with disabilities and those requiring additional support.